The Algorithm as Author: Viktor Pelevin and Russian Post-Cyberpunk Aesthetics. - Dinu, Camelia (Caietele Echinox, 2025)
The present study focuses on Viktor Pelevin's 2017 novel iPhuck 10 in terms of its post-cyberpunk features which have, to date, been understudied. We begin by comparing the cyberpunk and post-cyberpunk paradigms and argue that Pelevin's more recent novels go beyond the canonical conventions of cyberpunk to embrace a post-cyberpunk aesthetic marked. We then analyze iPhuck 10 through four major thematic threads: the redefinition of the human in relationship to artificial intelligence, the transformation of technology in the medium of consciousness, the dissolution of the corporeal body, and the critique of post-Soviet society. This study aims to demonstrate that the use of posthuman and post-Soviet motifs in iPhuck 10 differentiates the novel from traditional (Western) cyberpunk narratives and thereby positions it as a key example of post-cyberpunk literature in contemporary Russian fiction.